Effects of squat training, jump training, and their combination on jump and sprint performance of team sports athletes: a systematic review with meta-analysis - Ulloa-Sánchez, P.; Thapa, R. K.; Hernández-Elizondo, J.; Sortwell, A.; Ramirez-Campillo, R. (The Journal of Strength and Conditioning Research, 2025)
The aim of this systematic review was to evaluate the effects of squat training, jump training, and their combination on jump and sprint performance of team sport athletes. Following PRISMA 2020 guidelines, random-effects model meta-analyses were used to calculate the effect size (ES). The risk of bias and the certainty of the evidence were evaluated using the PEDro and GRADE scales, respectively. Electronic searches retrieved 131 peer-reviewed articles for meta-analyses involving trained/developmental to elite/international level male and female athletes (n = 4,237). Interventions lasted between 4 and 16 weeks, with 1-4 sessions per week. Studies reported a low risk of bias (median 7 points), although GRADE analyses revealed low to very low certainty of the evidence. Compared with controls, squat training at 80-95%, 80-90%, and 45-70% of 1RM improved jump height, acceleration (e.g., =15-m linear sprint time), and maximal velocity sprinting (e.g., 20-60 m linear sprint time) (ES = 0.69-1.18; p < 0.001-0.012, = 0-70%). Jump training improved jump height, acceleration, and maximal velocity (ES = 0.47-1.52, p < 0.001-0.016, = 11-86%). Combination of isolated squat (=75% 1RM) + jump training improved jump height and maximal velocity (ES = 0.55-0.65, p < 0.001, = 0-11%), while squat combined with other resistance training exercises + jump training improved jump height, acceleration, and maximal velocity (ES = 1.02-1.11; p < 0.001; = 54-76%). Differences between training types were determined by within-group analyses, revealing similar effects on jump height, acceleration, and maximal velocity. In conclusion, squat training, jump training, and their combination seem to be equally effective in improving jump and sprint performance in team sports athletes.